Metabolic Dysfunction of Astrocyte: An Initiating Factor in Beta-amyloid Pathology? - Yan, Liang-Jun (2013)
Astrocytes, the most important energy regulator in the brain, support brain energy needs. In the meantime, numerous studies have demonstrated that impaired brain glucose metabolism is closely linked to abnormal astrocytic metabolism in AD. Indeed, the interaction between amyloid plaques and perturbed astrocytic homeostasis contributes to AD pathogenesis and astrocytic metabolic dysfunction is thought to be a trigger for Aβ pathology through oxidative stress and neuroinflammation Moreover, astrocytic metabolic dysfunction may regulate Aβ generation via modulating proteolytic processing of amyloid precursor protein (APP) by β-secretase, γ-secretase, and α-secretase, and may also modulate APP post-translational modifications such as glycosylation, phosphorylation, and tyrosine sulfation. While it is known that metabolic dysfunction of astrocytes contributes to the failure of Aβ clearance, it has also been reported that such dysfunction has neuroprotective property and exhibits no detrimental outcomes. Therefore, the exact role of astrocytic metabolic dysfunction in Aβ pathology remains to be further investigated.